Kegiatan Pengabdian Masyarakat dalam Penyelenggaraan Kegiatan Tahsin Tilawah Al-Qur’an sebagai Upaya Penyempurnaan Bacaan Santri - Eli Masnawati; Intan Alfia Rahmawati (Universitas Sunan Drajat Lamongan, Indonesia, 2026)
Reading the Qur’an accurately and fluently in accordance with the rules of tajwid and tartil is a fundamental competence that must be mastered by santri as part of Islamic education in Islamic boarding schools. However, preliminary observations at LEI (Ludfie Ekolistik Institute) of Pondok Pesantren Tambak Bening Surabaya revealed that a number of santri still experience difficulties in reading the Qur’an properly due to differences in religious educational backgrounds, limited intensive guidance, and the shortage of qualified tahsin instructors. This community service program aimed to improve the quality of santri’s Qur’anic reading through a Qur’an Reading Assistance Program in the form of tahsin tilawah activities. The program employed the Asset-Based Community Development (ABCD) approach, implemented through preparation, implementation, and evaluation stages. The tahsin activities were conducted through both group-based and individual mentoring using an applied tajwid method tailored to the santri’s reading abilities. The results indicate a significant improvement in santri’s Qur’anic reading skills, particularly in terms of makhārij al-ḥurūf, accuracy of tajwid, and reading fluency. Furthermore, the program enhanced santri’s motivation and spiritual awareness of the importance of proper Qur’anic recitation as an act of worship. This activity also represents the implementation of the Tri Dharma of Higher Education and strengthens the synergy between universities and Islamic boarding schools in developing Qur’an-based Islamic education